2016
DOI: 10.1021/acs.jpclett.6b02102
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Single-Molecule Stokes Shifts: Influence of Conformation and Environment

Abstract: We report on time-dependent Stokes shift measurements of single molecules. Excitation and emission spectroscopy were applied to study the temporal Stokes shift evolution of single perylene diimide molecules embedded in a polymer matrix on the time scale of seconds. The Stokes shift varied between individual molecules as well as for single molecules undergoing different conformations and geometries. From the distribution and temporal evolution of Stokes shifts, we unravel the interplay of nanoenvironment and mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…These are clear indications of selective dye aggregation in the solid state, [63] though in the case of PTDI spectral changes could also originate from the variation of the twisting angle θ between its two naphthalene monoimide units with the rigidity of the environment (Scheme S1, Supporting Information). [64] In addition, concomitant changes in fluorescence intensity were observed when cooling down the system below T m , which are consistent with the activation of the AIE, ACQ, and PET processes as a result of molecular aggregation and, for the first time, demonstrate the capacity to control these luminescence switching mechanisms using PCMs and readily available dyes (Figure 3b and Table S1, Supporting Information). Thus, the strong TPE emission registered in solid EC (λ em,max = 445 nm) was nearly quantitatively lost upon melting (ΔF = −98.5%), which we ascribed to selective AIE upon PCM crystallization.…”
Section: Generalization Of Nir-induced Fluorescence Modulation In Pcmssupporting
confidence: 73%
See 1 more Smart Citation
“…These are clear indications of selective dye aggregation in the solid state, [63] though in the case of PTDI spectral changes could also originate from the variation of the twisting angle θ between its two naphthalene monoimide units with the rigidity of the environment (Scheme S1, Supporting Information). [64] In addition, concomitant changes in fluorescence intensity were observed when cooling down the system below T m , which are consistent with the activation of the AIE, ACQ, and PET processes as a result of molecular aggregation and, for the first time, demonstrate the capacity to control these luminescence switching mechanisms using PCMs and readily available dyes (Figure 3b and Table S1, Supporting Information). Thus, the strong TPE emission registered in solid EC (λ em,max = 445 nm) was nearly quantitatively lost upon melting (ΔF = −98.5%), which we ascribed to selective AIE upon PCM crystallization.…”
Section: Generalization Of Nir-induced Fluorescence Modulation In Pcmssupporting
confidence: 73%
“…A similar effect was encountered for the mixture of PTDI and DMA in OC, whose fluorescence intensity strikingly increased when heating above T m (λ em,max = 592 nm, Δ F = +4641%). However, this result could not be ascribed to ACQ, as intense redshifted PTDI fluorescence was measured in solid OC in the absence of DMA, which could be attributed to highly emissive J ‐aggregates [ 63 ] and/or variation of the internal twisting angle of isolated dye molecules [ 64 ] (Figure S6, Supporting Information). Therefore, PET‐induced fluorescence quenching arising from selective PTDI‐DMA interaction in the solid state should account for the emission modulation measured in this case.…”
Section: Resultsmentioning
confidence: 99%
“…The distribution of these localized states is influenced by the local energetic environment, trap states and variability of conjugation length . In a previous work, we showed that even identical chromophores can have different absorption and emission energies due to the energetic disorder of the local environment in a polymer film . However, we now assume similar spatial disorder, energetic disorder and trap states in the films and only discuss the influence of chromophore distribution.…”
Section: Discussionmentioning
confidence: 96%
“…the polarity as illustrated for Nile Red in different matrices. In combination with optimized polarization optics our approach should also be realizable at the single molecule level where the nanoscopic environment leads to strong heterogeneities in the measured Stokes shift [22]. The presented approach can enhance the currently established hyperspectral imaging methods in the fields of life and materials science imaging.…”
Section: Discussionmentioning
confidence: 99%
“…cells [6][7][8][9][10][11][12], chromosomes [13,14], organic tissue [15][16][17][18], or nanomaterials [19][20][21]. While measuring spatially resolved emission spectra has become relativity standard in many laboratories, measuring excitation spectra is more challenging since it requires a tunable excitation source or an interferometer in the excitation path [22,23]. Examples of combining emission and excitation spectroscopy simultaneously are even scarcer [24][25][26].…”
Section: Introductionmentioning
confidence: 99%